Establishment of Drosophila imaginal precursor cells is controlled by the Arrowhead gene. - Curtiss, J.; Heilig, J.S. (Development, 1995)
Metamorphosis in Drosophila melanogaster requires synchronization of numerous developmental events that occur in isolated imaginal precursor tissues. The imaginal primordia are established during embryonic stages and are quiescent for much of larval life. The Arrowhead gene is necessary for establishment of proper numbers of cells within a subset of imaginal precursor tissues. Loss-of-function mutations in Arrowhead reduce the number of abdominal histoblasts and salivary gland imaginal ring cells before the proliferative stages of their development. The number of abdominal histoblasts in mutant animals is approximately half that of wild-type, as might result from failure of a single early division of these cells. A neomorphic Arrowhead allele results in the specific loss of the retinal precursors by the early third instar, before they have begun to differentiate. Since Arrowhead mutations affect only subsets of imaginal tissue, there must be distinctions in the developmental regulation of different imaginal precursors. Arrowhead may be part of a regulatory pathway responsible for establishing the proper number of abdominal histoblasts and salivary gland imaginal ring cells. The neomorphic Arrowhead allele, which may cause misexpression of the Arrowhead gene in the eye-antenna imaginal disc, interferes with the establishment or proliferation of retinal precursor cells.